Study of Risk Factors and Assessment of Hematotoxicity and Oxidative Stress Among Women Stroke Patient with Metabolic Syndrome - Samir, Derouiche; Saadia, Salem; Maroua, Leguemairi (Dhaka University Journal of Pharmaceutical Sciences, 2022)
This study aims at evaluating some risk factors and the variation of certain hematological and oxidative stress markers in women with stroke disease. The observation (clinical study) was done on 130 voluntary women, divided into metabolic syndrome patients with and without stroke disease. Risk factors were estimated by Chi-square test. Results demonstrated that the high levels of family stress, self-medication and anticoagulants treatment were the most dangerous risk factors to stroke diseases, whereas brushing of teeth daily had an important protective factors against participants from disease. From biological study, results showed that RBC, hemoglobin, GSH and total thiol levels were significantly decreased (p<0.05) while WBC, neutrophile, platelet, MDA, SOD, ORAC and vit C levels were significantly increased (p<0.05) in women with metabolic syndrome (MS) + stroke patients as compared to MS patients without stroke. In conclusion, several socioeconomic and clinical factors contributed to the dispersion and development of the stroke. In addition, oxidative stress during metabolic syndrome contributes to the development of stroke disease. Dhaka Univ. J. Pharm. Sci. 21(2): 195-203, 2022 (December)